Cytokinins and Expression of SWEET, SUT, CWINV and AAP Genes Increase as Pea Seeds Germinate - Jameson, Paula E; Dhandapani, Pragatheswari; Novak, Ondrej; Song, Jiancheng (International journal of molecular sciences, 2016)
Transporter genes and cytokinins are key targets for crop improvement. These genes are active during the development of the seed and its establishment as a strong sink. However, during germination, the seed transitions to being a source for the developing root and shoot. To determine if the sucrose transporter (SUT), amino acid permease (AAP), Sugar Will Eventually be Exported Transporter (SWEET), cell wall invertase (CWINV), cytokinin biosynthesis (IPT), activation (LOG) and degradation (CKX) gene family members are involved in both the sink and source activities of seeds, we used RT-qPCR to determine the expression of multiple gene family members, and LC-MS/MS to ascertain endogenous cytokinin levels in germinating Pisum sativum L. We show that genes that are actively expressed when the seed is a strong sink during its development, are also expressed when the seed is in the reverse role of being an active source during germination and early seedling growth. Cytokinins were detected in the imbibing seeds and were actively biosynthesised during germination. We conclude that, when the above gene family members are targeted for seed yield improvement, a downstream effect on subsequent seed germination or seedling vigour must be taken into consideration.
Keywords: Cytokinins; cytokininy; Gene Expression Regulation, Plant; germination; beta-Fructofuranosidase; invertasa; hrách setý; semenáček; regulátory růstu rostlin; Seeds; buněčná stěna; Amino Acid Transport Systems; Monosaccharide Transport Proteins; Pisum sativum; semena rostlinná; Seedlings; klíčení; Tandem Mass Spectrometry; Germination; proteiny přenášející monosacharidy; regulace genové exprese u rostlin; tandemová hmotnostní spektrometrie; transportní systémy aminokyselin; Plant Growth Regulators; cytokinin; Cell Wall